2002
DOI: 10.1074/jbc.m207003200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Consequences of Mutating Cysteine Residues in the Amino Terminus of Human Multidrug Resistance-associated Protein 1

Abstract: Multidrug resistance-associated protein 1 (MRP1) is a member of the ATP-binding cassette membrane transport superfamily and is responsible for multidrug resistance in cancer cells. Currently, there are nine known human MRPs. Distinct from many other members of the ATP-binding cassette superfamily, human MRP1 and four other MRPs have an additional membrane-spanning domain (MSD) with a putative extracellular amino terminus. The functional significance of this additional MSD (MSD1) is currently unknown. To unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 44 publications
1
66
1
Order By: Relevance
“…Notwithstanding evidence indicating that N-terminal deletion of the entire MSD0 does not alter several properties of the pump, it is anticipated that this domain has functions that have yet to be uncovered. Studies showing that MRP1 activity can be affected by point mutations in the extracellular portion of the N-terminus and in MSD0, and by N-terminal deletions that extend to and include the first transmembrane domain hint at this possibility, although it remains to be determined whether these perturbations influence actual drug binding and transport as opposed to preventing the assumption of correct topology in the plasma membrane (Gao et al, 1998;Yang et al, 2002;Leslie et al, 2003b).…”
Section: Mrp1mentioning
confidence: 99%
“…Notwithstanding evidence indicating that N-terminal deletion of the entire MSD0 does not alter several properties of the pump, it is anticipated that this domain has functions that have yet to be uncovered. Studies showing that MRP1 activity can be affected by point mutations in the extracellular portion of the N-terminus and in MSD0, and by N-terminal deletions that extend to and include the first transmembrane domain hint at this possibility, although it remains to be determined whether these perturbations influence actual drug binding and transport as opposed to preventing the assumption of correct topology in the plasma membrane (Gao et al, 1998;Yang et al, 2002;Leslie et al, 2003b).…”
Section: Mrp1mentioning
confidence: 99%
“…A truncated mutant, which lacks this domain, was functional with respect to transport activity, and similarly to the wild-type protein, localized to the basolateral membrane in polarized cells [6]. On the other hand, certain mutations in TMD0 resulted in significant conformational changes and reduced transport activity [59,180]. Based on these observations, it has been suggested that certain residues in TMD0 contribute to the maintenance of the correct structure of the protein.…”
Section: Structure Of Mrp1 and The Role Of The Amino-terminal Regionsmentioning
confidence: 99%
“…HEK293-transfected sublines HEK293/ Vec (18), HEK293/ABCC1 (19), and HEK293/ABCG2 (20) were obtained from Prof. Jian-ting Zhang (Indiana University Simon Cancer Center, Indianapolis, IN). The human breast cancer cell line MCF-7 and the mitoxantrone selected MDR cell line MCF-7/MX (21) were kindly provided by Dr. E. Schneider (Wadsworth Center, Albany, NY).…”
Section: Cell Culture Treatments and Lysate Preparationsmentioning
confidence: 99%